Rice Marketing Systems Model to Strengthen Institutional of Rice Marketing in Lampung Province Indonesia - Noer, Irmayani; Unteawati, Bina (Asia Pacific Journal of Management and Education (APJME), 2022)
A marketing system is efficient if it is able to deliver production results to consumers at the lowest possible cost and relatively even margins to the actors involved. But in reality, when production is in surplus while demand is not, it causes the market mechanism to produce price distortions. This study aims to analyze the rice marketing system with an organizational approach and market demand (market trends, market demand functions, and price elasticity). The data is obtained from the relevant authorities as well as from observations and internet searches. The results showed that the marketing actors for unhusked rice/rice consisted of collectors, rice millers, inter-district traders, and retailers where almost half of the profits were enjoyed by rice mills. The results of the market demand function analysis show that rice consumption will tend to decrease if there is an increase in rice prices. Consumers will divert some of their consumption expenditure on rice substitute products. The results of market trend analysis show that rice consumption has a positive trend over time. Keywords:  Market Demand,  Market Trends, Organizational Approach, Price Elasticity, Rice Marketing System.